Fuzzy voice classifier and fuzzy voice pathology identification system - Sathees Kumar, Nataraj; Sazali, Yaacob, Prof. Dr.; Ahamad Nazri, Abdullah (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.